C-Reactive Protein (CRP) Levels in Stadium 5 Chronic Kidney Disease with Hemodialysis Regularly and Covid-19 - Alifa, Cut Safira; M. Feldi Gazaly Nasution (TALENTA Publisher, Universitas Sumatera Utara, 2023)
Background: Chronic Kidney Disease (CKD) is kidney dysfunction that has occurred for more than 3 months. Patients with stage 5 CKD with hemodialysis (HD) regularly are prone to suffering from COVID-19 because hemodialysis patients can experience malnutrition, inflammation, and atherosclerosis. This study aims to determine CRP levels in stage 5 CKD with HD) regularly and COVID-19 at USU Hospital from June to October 2021. Method: One of the inflammatory biomarkers that can be used in assessing C-Reactive Protein (CRP) levels, by looking at these levels it is expected to know how severe the inflammation of the disease is. This is an observational descriptive study with a total sampling technique. Data were obtained secondarily from the medical records of stage 5 chronic kidney disease patients with COVID-19 with HD regularly. Result: Of the total 28 data, there were male 23 (82.1%) and female.5 (17.9%) patients. Most of them have aged 40-60 years old, and the clinical picture of patients was shortness of breath, with comorbid hypertension. In this study, the most HD duration was for 12-36 months and the highest level of CRP is > 200 mg/dl. Conclusion: The patients with CKD with HD regularly and covid-19 have increased inflammatory markers of CRP